Small and Medium Sized Businesses Strategy Improving in Sustainability Transformation in Agrobussines Sector Industry in DKI Jakarta Area, Indonesia - IGP Ratih Andaningsih; Trinandari Prasetya Nugrahanti; Novita Novita (Ilomata International Journal of Management, 2023)
The purpose of research is to give contribution of SMEs in strategies and development in agrobusiness sector industry and environmental sustainability of agrobusiness sector.This research analyses small and medium sized businesses strategy improving in sustainability transformation in agrobussines sector industry in DKI Jakarta . The business agriculture needs solution environment and sustainability and transformation development business sector of of agriculute industry certain characteristics.Transformation practically development sector business industry one of the efforts to improve competence and skill and full support from government..This research uses with qualitative description and content analysis methode agrobusiness industry sustainability with in busines agriculture industry with 25 respondens. This agriculture environmentally sustainability business for SMEs focus to improving SMEs agrobusiness industry We summarize the SMEs Agrobusiness sector for development for SMEs Business especially agrobusiseness industry. The limitation of this research is that it is limited to the SMEs business transformation strategy for the sustainability of the agribusiness sector in DKI Jakarta Indonesia.. Thismaterial of sustainability agrobusiness industry and give added value to improving and development longterm progame sustainability agrobusiness..This research provides benefits and opportunities in agrobussines especially in development and implication to the realities of agrobusiness industry sector.